2017
DOI: 10.1371/journal.pmed.1002316
|View full text |Cite
|
Sign up to set email alerts
|

Risk of hospitalization with neurodegenerative disease after moderate-to-severe traumatic brain injury in the working-age population: A retrospective cohort study using the Finnish national health registries

Abstract: BackgroundPrevious epidemiological studies suggest that working-aged persons with a history of moderate-to-severe traumatic brain injury (TBI) may have an increased risk for developing neurodegenerative disease (NDD) while persons with a history of mild TBI do not. In this comprehensive nationwide study in Finland, we assessed the risk of NDD and history of moderate-to-severe TBI in the working-age population.Methods and findingsWe performed a population-based follow-up study using the Finnish Care Register fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 38 publications
2
53
0
3
Order By: Relevance
“…В настоящее время основная концепция черепно-мозговой травмы складывается вокруг представления о ней как о динамическом процессе, которая запускает целый каскад процессов и биохимических реакций, которые обусловливают ее последствия [7,12,25]. Повреждение головного мозга может быть опосредовано токсическим действием клеточного кальция, свободными радикалами и многими другими биохимическими процессами в постравматический период реконвалесценции [26].…”
Section: ◊ результаты и их обсуждениеunclassified
See 2 more Smart Citations
“…В настоящее время основная концепция черепно-мозговой травмы складывается вокруг представления о ней как о динамическом процессе, которая запускает целый каскад процессов и биохимических реакций, которые обусловливают ее последствия [7,12,25]. Повреждение головного мозга может быть опосредовано токсическим действием клеточного кальция, свободными радикалами и многими другими биохимическими процессами в постравматический период реконвалесценции [26].…”
Section: ◊ результаты и их обсуждениеunclassified
“…Риск развития деменции обычно связывают с умеренной и тяжелой черепно-мозговой травмой, однако не исключается такая связь и с легкой черепно-мозговой травмой [5,14,23,25]. Психоз, вторичный по отношению к черепно-мозговой травме, считается редким и тяжелым последствием черепно-мозговой травмы, встречаясь у 4,0-8,9 % лиц и появляются в три раза чаще, чем в общей популяции [14,16].…”
Section: ◊ результаты и их обсуждениеunclassified
See 1 more Smart Citation
“…However, a study using Swedish data on head injuries who reported that 3.4% of all Sweden's A&E admissions were related primarily to a head injury. 63 Using this figure as a denominator, to estimate the possible head injury in the UK general public, we examined A&E data for England to find that there were 5.5 million people with at least one over-night stay. [63][64][65][66] Thus if 3.4% of English A&E admissions were head injuries, as in Sweden, this gives us approximately 187,000 who had a head injury.…”
Section: Macro Contextmentioning
confidence: 99%
“…MS-related disability limits participation in everyday activities and has a considerable impact on quality of life, thereby affecting productivity and employment. Due to the constantly growing number of patients, this disease has major socio-economic consequences and is a significant public health problem [2,3].…”
Section: Introductionmentioning
confidence: 99%